MEAT CONSUMPTION PRACTICE IN CHINA: AN EMPIRICAL ANALYSIS BASED ON ELASTIC THEORY - Y. J. Xue; J. L. Yan; H. F. Zhao1; C. H. Ma (Journal of Animal and Plant Sciences, 2021)
Meat consumption elasticity coefficient can reflect the processing traces of living standard. This paper analyzes these coefficients of urban and rural residents in China with the AIDS (Almost Ideal Demand System Model). Meat consumption structure of residents has begun to show signs of adjustment following their respective trajectories, which has been discussing in academic but lacks theoretical proof for decade years. Based on elastic theory, we have provided favorable evidence for this fact, and we found: (1) Elasticity coefficients show both urban and rural residents have been all sensitive to price, especially the city dwellers. The Urban residents is more sensitive to poultry than others. Rural residents have long been more interested in pork, though the mutton has been the trustiest. (2) Income and meat price are two main causes affect meat consumption, but there is no significant positive correlation between meat consumption and disposable income in Urban, different from Rural. With the income increasing, the kinds and quality of meat in basket of different residents are changing. (3) Furthermore, meat consumptions between urban and rural residents are not synchronized, and even sometimes the trends show the opposite directions because of income, habits, etc.
Keywords: Meat consumption; Elasticity; AIDS